UPAYA PENINGKATAN KEMANDIRIAN SOSIAL EKONOMI INDIVIDU EKS PSIKOTIK MELALUI PELATIHAN KECAKAPAN VOKASIONAL DI UPT REHABILITASI SOSIAL EKS PSIKOTIK PROVINSI JAWA TIMUR - Chotim, Muh.; Christiana, Ratih; Pratama, Andika Hady (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Ex-psychotic individuals encounter many difficulties in the process of socializing and returned to the environment, so that the necessary training skills before returning to the family and society. The purpose of this study was (1) To determine the effort to improve the social and economic independence of individual ex-psychotic through vocational skills training in the Social Rehabilitation Unit Ex Psychotic Social Service of East Java Province, (2) To determine the effectiveness of vocational skills training to improve social and economic independence of the individual ex-psychotic The Social Rehabilitation Unit Ex Psychotic Social Service of East Java Province. Writing method using a case study approach to field studies (field research) combined with literature (library research). This community service is a descriptive research, data analysis using qualitative analysis with interactive model. The analyzed data is the data rate of socio-economic independence of individuals before and after the psychotic ex vocational skills training. This research with two activities that make the carpet of material raffia rope and wooden crafts. Potential outcomes include training in order to improve their socio-economic independence, product copyrighted works, a national scientific journals and strengthening the role of counselors and social services functions.Â Keywords: Independence, Social, Economic, Ex Psychotic, Vocational